2022
DOI: 10.1051/matecconf/202236404018
|View full text |Cite
|
Sign up to set email alerts
|

Actual achievements and future challenges of HPFRC for structural rehabilitation of bridges

Abstract: The state of road infrastructures in many advanced countries is rapidly changing under the impulse of massive funding from governments, eager to have more efficient and safer transportation systems. The use of well-known materials such as fibre-reinforced concrete (FRC) is finding a growing space for structural rehabilitation of bridges; the adopted material is often defined as High performance fibre reinforced concrete (HPFRC) due to its enhanced performance. The paper presents the principal findings of an EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…When loading exceeds 70% of concrete strength capacity, the concrete behaves differently due to reaching non-elastic stage [3]. In the non-elastic stage, the concrete exhibits internal damage and will be permanently deformed, which indicates the end of service life.…”
Section: Effect Of Substrate Damage Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…When loading exceeds 70% of concrete strength capacity, the concrete behaves differently due to reaching non-elastic stage [3]. In the non-elastic stage, the concrete exhibits internal damage and will be permanently deformed, which indicates the end of service life.…”
Section: Effect Of Substrate Damage Levelmentioning
confidence: 99%
“…In addition, they are much cheaper than steel plates and fibre-reinforced polymer (FRP) jacketing solutions. Studies have shown that HPFRC jackets improve the load-bearing capacity, ductility, energy dissipation, and durability of concrete structures [2,3]. Nevertheless, the strength enhancement due to HPFRC jacketing and the relationship between the normal strength concrete (NSC) substrate and HPFRC jacket are unclear.…”
Section: Introductionmentioning
confidence: 99%